ASK LDT 2.0: A web-based graphical tool for authoring learning designs - Zervas, P.; Fragkos, K.; Sampson, Demetrios (IADIS, 2013)
During the last decade, Open Educational Resources (OERs) have gained increased attention for their potential to support open access, sharing and reuse of digital educational resources. Therefore, a large amount of digital educational resources have become available worldwide through web-based open access repositories which are referred to as Learning Object Repositories (LORs). These resources have the potential to facilitate teachers to improve and enhance their day-to-day teaching activities. On the other hand, it has been identified that teachers could benefit from their participation in communities of best teaching practices by sharing, not only educational resources, but also learning designs that represent their pedagogical approach. As a result, there is an increased interest for the development of web-based repositories that facilitate open access to both educational resources and learning designs. However, the process of developing and sharing learning designs through web-based repositories requires authoring tools that can represent learning designs in a machine-readable way. A commonly accepted way that provides a standard notation language for the description of learning designs is the IMS Learning Design (LD) Specification. Consequently, a number of IMS LD compatible learning design authoring tools has already been developed. Nevertheless, most of these tools (a) are not supporting the process of importing and editing learning designs and (b) they are stand-alone tools restricting their widespread use. To this end, in this paper we present a web-based learning design authoring tool that aims to overcome the previous identified problems.